The highly accuracy of lymphocyte count in diagnosing influenza A in children during the influenza A season - Chen, Houyu; Cui, Penghao; Jin, Haifeng; Guo, Yan; Huang, Yi; Jiao, Feng; Yang, Xiaotao; Wang, Yanchun; Luo, Yonghan (Frontiers in Pediatrics, 2025)
ObjectiveTo study the value of lymphocyte count in early diagnosis of influenza A in children during the influenza A season.MethodsWe selected children aged 0–18 years diagnosed with influenza A who visited the outpatient clinic of Kunming Children's Hospital during the influenza A epidemic in China from March to April 2023 as the case group (influenza group) and matched them with healthy children undergoing physical examinations as the control group. We collected complete complete blood count within 48 h of disease onset in children with influenza A and compared these parameters with those of the control group. Receiver operating characteristic (ROC) curve analysis, restricted cubic spline functions, and decision curve analysis (DCA) were employed to assess diagnostic performance and clinical utility.ResultsThe results showed that there were 541 children in the influenza group and 597 in the control group, with no statistically significant differences in age and gender distribution between the two groups (P > 0.05). Significant differences (P < 0.05) were observed in white blood cell count (WBC), neutrophil percentage, neutrophil count, lymphocyte percentage, lymphocyte count, monocyte percentage, monocyte count, platelet count (PLT), and C-Reactive Protein (CRP) between the two groups. ROC curve analysis indicated that lymphocyte count had the highest diagnostic accuracy for influenza A, with a Receiver-operating-characteristic curve (AUC) of 0.926 (95% CI 0.9113–0.9413) and an optimal cutoff value of 1. 812 × 109.Subgroup analyses stratified by age revealed consistently high AUC values. Dose-response analysis demonstrated a significant non-linear relationship between lymphocyte count and influenza A infection risk (nonlinear test, P < 0.001). DCA indicated favorable clinical applicability of lymphocyte count as a predictive marker.ConclusionDuring the influenza A epidemic, a decrease in lymphocyte count within 48 h of onset can serve as an indicator for early detection and diagnosis of pediatric influenza A.